1969
DOI: 10.4319/lo.1969.14.4.0521
|View full text |Cite
|
Sign up to set email alerts
|

Release of Dissolved Organic Matter by Marine Seaweeds and Distribution of Their Total Organic Production to Inshore Communities1

Abstract: Under controlled experimental conditions, release rates of organic matter were estimated for five species of Barents Sea macrophytes and for thirteen species of Black Sea macrophytes. The release rates of different species from the Barents Sea were bctwccn 0.9 and 2.9 mg of organic matter per gram (dry wt) of plants per hour (mg g-l hr-") in March and between 1.7 and 9.8 mg 6-l hr-' in June. The release rates of different species from the Black Sea were between 1.25 and 6.1 mg g-l hrzL in fast growing plants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(92 citation statements)
references
References 1 publication
4
87
1
Order By: Relevance
“…The amount of primary productivity that must go rather quickly to DOC to support this bacterioplankton is an example. When Khailov & Burlakova (1969) and Sieburth (1969) reported that up to 40 ~ of the photosynthesis of the large browns is released during the early spring, this was challenged by Mann (1974) and Moe:bus & Johnson (1974) among others. However, current work at Dalhousie by Mann and a Ph.D. student and by Johnston et al (1977) using independent methods show that for Larninaria a release of 30 to 40 % of production occurs when photosynthesis occurs but growth has not yet begun, so that the plants dump the excess.…”
Section: Discussionmentioning
confidence: 98%
“…The amount of primary productivity that must go rather quickly to DOC to support this bacterioplankton is an example. When Khailov & Burlakova (1969) and Sieburth (1969) reported that up to 40 ~ of the photosynthesis of the large browns is released during the early spring, this was challenged by Mann (1974) and Moe:bus & Johnson (1974) among others. However, current work at Dalhousie by Mann and a Ph.D. student and by Johnston et al (1977) using independent methods show that for Larninaria a release of 30 to 40 % of production occurs when photosynthesis occurs but growth has not yet begun, so that the plants dump the excess.…”
Section: Discussionmentioning
confidence: 98%
“…A second explanation involves some kind of resource/signal interaction between Zostera noltii and Ulva rigida canopies. Macroalgae can release a variable amount of their daily fixed carbon as DOC (Khailov & Burlakova 1969, Otsuki & Wetzel 1974, Pregnall 1983). This DOC is usually composed of low molecular weight molecules like carbohydrates, organic nitrogen, polyphenols and halocarbons (Sieburth 1969, Wetzel & Penhale 1979, Nightingale et al 1995, which can be used as a source for plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…This stock solution was assumed to represent natural yellow substance produced in the ocean. Exudates from Norwegian seaweeds have been reported to contain yellow substance that is indistinguishable from that in seawater (Sieburth and Jensen 1969) and Khailov and Burlakova (1969) have shown that release from seaweeds can be a significant contribution to inshore waters. Clay was obtained from shelf mud (courtesy of J. Christensen) at 43"N, 68"W in the Gulf of Maine during a cruise in July 1987.…”
Section: Acknowledgmentsmentioning
confidence: 99%